2023
DOI: 10.1111/tmi.13863
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen inactivation methods to prevent transfusion‐transmissible arboviruses: A systematic review and meta‐analysis

Abstract: Objective: Arboviruses are emerging as a relevant threat to transfusion safety. Pathogen inactivation methods (PIMs) may reduce the risk of transmission through transfusion, as long as they meet minimum standards for effectiveness. This study aims to assess the log reduction of viral load achieved with different PIMs, according to the blood product they are used on and the arbovirus targeted. Methods: Systematic literature review and meta-analysis. Searches were conducted in MEDLINE and Embase. The study proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
6
2
Order By: Relevance
“…Similar trends have been observed in various regions, such as the Philippines, French Polynesia, Puerto Rico, Brazil, Bolivia, Guadeloupe, Martinique, and the Dominican Republic, with anti-DENV IgG seroprevalence exceeding 80% in healthy blood donors. 25 In comparison to the general population, the seropositivity in this study is higher than that reported among individuals residing in central and southern Thailand (79%). 17 Regarding IgM antibodies against DENV, the prevalence in blood donor populations ranges from 0% to 13.5%, 25 with the highest reported value in India, followed by Brazil.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Similar trends have been observed in various regions, such as the Philippines, French Polynesia, Puerto Rico, Brazil, Bolivia, Guadeloupe, Martinique, and the Dominican Republic, with anti-DENV IgG seroprevalence exceeding 80% in healthy blood donors. 25 In comparison to the general population, the seropositivity in this study is higher than that reported among individuals residing in central and southern Thailand (79%). 17 Regarding IgM antibodies against DENV, the prevalence in blood donor populations ranges from 0% to 13.5%, 25 with the highest reported value in India, followed by Brazil.…”
Section: Discussioncontrasting
confidence: 69%
“…25 In comparison to the general population, the seropositivity in this study is higher than that reported among individuals residing in central and southern Thailand (79%). 17 Regarding IgM antibodies against DENV, the prevalence in blood donor populations ranges from 0% to 13.5%, 25 with the highest reported value in India, followed by Brazil. Several studies also tested donors in endemic regions or areas experiencing an epidemic outbreak using the dengue NS1 antigen, revealing a prevalence from 0% to 5.3%.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Such risk may be further mitigated by applying PR technology. In addition, applying PR to platelets in the setting of arboviruses outbreaks, notably those associated with a transfusion risk such as West Nile virus [14], allows for an immediately available alternative to specific testing or targeted donor deferral [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to malaria and Zika viruses, they are transmitted through the bite of infected Aedes species mosquitoes. While the dengue virus and the chikungunya virus are not prevalent in Europe or the continental United States, outbreaks in Asia, Pacific countries, South and Central America, and Caribbean islands have raised concerns about transfusion transmission in those regions and among returning travellers [ 56 , 57 ].…”
Section: Viral Transmissionmentioning
confidence: 99%